STUDI PENERAPAN PROGRAM PEMBANGUNAN INFRASTRUKTUR PEDESAAN (PPIP) DI KECAMATAN KOTO BALINGKA KABUPATEN PASAMAN BARAT - Faradona, Wilia Meri; Ahmad, Ridwan; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
This research is motivated by the application of Rural Infrastructure Development Programme (PPIP) in Koto Balingka at West PasamanDistrict uneven. This is one of the triggering factors the onset of problems in society. This study intentto obtain the data, processing,analyze and discuss data on the implementation of Rural Infrastructure Development Programme (PPIP) in Koto Balingka at West PasamanDistrict.Type of this research is descriptive. The population in this research about 6,410 people that all people in Koto Balingka at West PasamanDistrict. The samples were taken through the area sampling and then taken the respondents sampling. Area sampling using purposive sampling, it means the sample of this research defined 4 rural. And the respondents sampling using proportional random sampling technique. Sample this reseach was 62 people. The Instrument that used was a questionnaire or a questionnaire. The analysis of data using the percentage formula and drawned out by TCR.The Results of this study found: 1) Human participation in the implementation of Rural Infrastructure Development Programme (PPIP) in Koto Balingka at West PasamanDistrict average achievement level is 3.95 with 79.02 % of respondents were agood enough category. 2) The condition of roads in the application after the development of Rural Infrastructure Development Programme (PPIP) in Koto Balingka at West PasamanDistrictaverage achievement level is 3.75 with 74.96 % of respondents werea good enough category. 3) Revenues in the implementation of the Rural Infrastructure Development Programme (PPIP) in Koto Balingka at West PasamanDistrict average achievement level is 3.83 with 76.5 % of respondents were a good enoughcategory.